PENGARUH FOOD BLOGGER INSTAGRAM PADA MINAT BERWISATA KULINER GENERASI MILENIAL - Julita (Journal of Tourism Destination and Attraction, 2022)
Promotion through social media has become an obligation for culinary business actors. Instagram social media which is dominated by millennial generation users can be used to find references for a food product, drink or even a restaurant. Through a quantitative descriptive method, with 130 respondents who were taken using a convenience sampling technique, and distributed using an online questionnaire, the result is that the millennial generation currently likes to view Instagram food blogger accounts. In this study, in analyzing the data using instrument testing, classical assumption test and multiple regression analysis. From hypothesis testing, it was found that the independent variable, namely the promotion of food blogger Instagram, which was divided into context, communication, collaboration, and connection, had a significant effect simultaneously on the millennial generation's culinary interest. The contribution of the influence of the Instagram food blogger promotion on the millennial generation's culinary tourism interest can be seen from the value of the coefficient of determination, which is 80.6%. However, partially the promotion of food blogger Instagram does not have a significant influence on the millennial generation's culinary travel interest. It is proven that only the content indicator on the Instagram food blogger promotion has a partial effect, namely with a tcount of 0.128 which is greater than ttable of 1.656 with a Sig value. of 0.899 > 0.05, which means that the content on the promotion of food blogger Instagram has a significant influence on the millennial generation's decision to take culinary tours.